THE INFLUENCE OF LIQUIDITY, PROFITABILITY, AND LEVERAGE RATIO ON DIVIDENDS PAYOUT RATIO (Empirical Study on Manufacturing Companies Listed in the Indonesia Stock Exchange on the Period of 2009 – 2011) - A’yuni, Qurrota; Irianto, Gugus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The objective of this research is to find out the influence of liquidity, profitability, and leverage ratio on Dividend Payout Ratio in Manufacture companies listed on IDX period 2009-2011. The liquidity ratio is represented by Current ratio, profitability ratio is represented in Return on Investement (ROI), and leverage ratio is represented by Debt to Equity ratio. The data used in this research are financial reports of 13 manufacture companies period 2009-2011 obtained from ICMD. Purposive sampling technique is used in order to get sample which is appropriate with the define criteria. The analysis tool used is multiple linear regression analysis. The result of the research shows that Current ratio, ROI, and Debt to Equity ratio simultaneously have significant influence on Dividend Payout ratio. The result also indicate that partially ROI has positive and significant influence on Dividend Payout ratio.Keywords:Â Dividend Payout ratio, Current ratio, Return on Investment, and Debt to Equity ratio